Makna Simbolik Mappacci Pada Masyarakat Bugis di Kabupaten Bone (Kajian Semiotika Charles Sanders Pierce) - Fatihah, Nur; Salam, Salam; Nurhusna, Nurhusna; Syamsudduha, Syamsudduha; Sakaria, Sakaria (SOCIETIES: Journal of Social Sciences and Humanities, 2023)
Abstract.  This study examines the symbolic meaning of a tradition and aims to describe the form of symbolic meaning contained in the mappacci tradition at Bugis traditional weddings in Bone Regency. This study uses a qualitative descriptive research method using Charles Sanders Pierce's semiotic analysis. The data in this study are in the form of symbolic meanings contained in the symbols used in the mappacci tradition of Bugis traditional marriages in Bone Regency. The source of the data in this study was the mappacci ritual procession for the traditional wedding of the Bugis tribe in Bone Regency and the people of Makassar who have in-depth knowledge of the mappacci event. Data collection techniques used in this study were direct observation, interview techniques, documentation techniques, and recording techniques. The results showed that mappacci contains a symbolic meaning as self-cleanliness and purity, which has the aim of cleansing the soul and body of the bride and groom before entering the household ark. The forms of symbolic meaning contained in the mappaci tradition are: 1) pillows have a symbolic meaning of mutual respect (sipakatau), honor and glory or dignity, 2) silk sarongs have a symbolic meaning of self-esteem, istikhamah and perseverance, 3) banana shoots have a meaning symbolic connecting or continuous, 4) jackfruit leaves have a symbolic meaning of noble ideals and hope, and honesty, 5) pacci leaves have a symbolic meaning of cleanliness and purity, 6) rice has a symbolic meaning of growing well, prosperous, and prosperous, 7 ) a candle has a meaning as a sulo matappa (sulo of life) or gives light to the path to be taken, 8) a pacci place or container has a symbolic meaning of unity, 9) water as a complement. Of the nine forms of symbolic meaning, these are arranged in one summary of words containing hopes and prayers for the welfare and happiness of the bride and groom in carrying out the household ark. Keywords: symbolic meaning, mappacci, semiotics